Hubungan Asi Eksklusif dengan Status Gizi Anak Usia 6-24 Bulan Di Wilayah Kerja Puskesmas Benteng Kabupaten Indragiri Hilir Tahun 2019 - Indah Dwi Aryani Indah Dwi Aryani; Syamsul Bahri Riva’i; Oktavia Dewi; Ika Putri Damayanti (LPPM Universitas Muhammadiyah Riau, 2019)
Abstract Nutritional status can be interpreted as a health status produced by a balance between nutritional needs and input. Nutritional status is largely determined by the availability of nutrients in sufficient quantities and in the right combination of time at the body cell level to develop and function normally. The purpose of this research is to know the relationship between exclusive breastfeeding and nutritional status of children aged 6-24 months in the working area of ​​Benteng Puskesmas, Indragiri Hilir Regency in 2019. This research is an observational analytic quantitative with the type of analytical cross section study. This research was conducted from June to July 2019. Data analysis was carried out in stages including univariate analysis, bivariate analysis and multivariate analysis. The sampling procedure is done by Purposive Sampling with Quota Sampling with a sample size of 220 toddlers. The results of multivariate analysis, the most influential variable was exclusive breastfeeding (POR = 5.263, 95% CI = 2.519-10.994) .. Education (POR = 4.146, 95% CI = 2.031-8.463). Family income (POR = 2,190, 95% CI = 1,068-4,491). The conclusion in this study is that exclusive breastfeeding, education, and income are related to nutritional status. It is expected that mothers who have toddlers to better understand and improve information and knowledge about exclusive breastfeeding and also about nutrition and nutrition for children aged 6-24 months.